2022
DOI: 10.1002/csr.2428
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social irresponsibility: What we know and what we need to know

Abstract: Corporate social irresponsibility (CSI) is a critical issue for managers and researchers. In fact, the number of studies on this subject from diverse literature is rapidly increasing, seeking to answer questions regarding the core elements of CSI, its antecedents, and consequences. This paper offers a comprehensive literature review of this topic, identifying and assessing previous studies, synthesizing their findings, and highlighting knowledge gaps. Additionally, it offers recommendations regarding how to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 193 publications
0
12
0
Order By: Relevance
“…Accordingly, we aim to add to the ongoing debate (Enciso-Alfaro & García-Sánchez, 2022; Iborra & Riera, 2022;Mio et al, 2022) and complement prior literature by conducting a systematic review of 173 published papers. In adopting the regime of the systematic literature review suggested by Aguilera et al (2021), our analysis was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we aim to add to the ongoing debate (Enciso-Alfaro & García-Sánchez, 2022; Iborra & Riera, 2022;Mio et al, 2022) and complement prior literature by conducting a systematic review of 173 published papers. In adopting the regime of the systematic literature review suggested by Aguilera et al (2021), our analysis was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Since the decision to disclose environmental information is not directly influenced by a firm's broader social and governance disclosure attitudes (Broadstock et al, 2018), there is a need to examine the determinants of environmental reporting in isolation from other dimensions of sustainability disclosure. Accordingly, we aim to add to the ongoing debate (Enciso‐Alfaro & García‐Sánchez, 2022; Iborra & Riera, 2022; Mio et al, 2022) and complement prior literature by conducting a systematic review of 173 published papers. In adopting the regime of the systematic literature review suggested by Aguilera et al (2021), our analysis was conducted according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…In respect to CSI, we add new evidence to the underdeveloped line of research that links individual level antecedents with CSI behaviors (Grijalva and Harms, 2014;Iborra and Riera, 2023). By focusing on the individual level instead of on institutional variables, we respond to the call made by Ghoshal (2005) that CEOs are not free from moral or ethical responsibility for their actions and, as shown, we have found empirical support for this argument.…”
Section: Discussionmentioning
confidence: 58%
“…corporate acts that intentionally cause harm (Clark et al, 2022;Kemp and Owen, 2022) -has relevant social, environmental and economic consequences impacting companies, communities and people worldwide. As Iborra and Riera (2023) state, there is empirical evidence that CSI provoked enormous consequences, between others, in CEO's narcissism and irresponsible behavior consumers-in emotions, attitudes or purchase intentions-(e.g. Antonetti, 2020;Valor et al, 2022), in firms' financial performance as well as in firms' reputation, trustworthiness and moral capital (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation